Cathode paste, its preparation and use

JP2024526553A5Inactive Publication Date: 2024-12-17VARTA MICROBATTERY GMBH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023577350
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-08-09
Filing Date
2022-07-19
Publication Date
2024-12-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The use of cathode pastes in lithium-ion cells is hindered by premature gelation due to the high hygroscopicity of materials like lithium nickel manganese cobalt oxide, leading to quality fluctuations and requiring complex, costly measures to prevent moisture exposure.

Method used

A cathode paste formulation using lithium mixed oxides with high nickel content, polyvinylidene difluoride as the electrode binder, and an organic additive component capable of neutralizing hydroxide ions with a boiling point between 50°C to 210°C, preventing crosslinking of PVDF and stabilizing the paste.

Benefits of technology

The formulation ensures stable viscosity over several weeks, simplifies processing, eliminates the need for complex moisture prevention measures, and maintains consistent cathode quality without altering the cathode's properties, thus reducing costs and improving manufacturing efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

In the cathode paste (1) for manufacturing a cathode of a lithium ion cell, the cathode paste contains, as an active material, a compound of the formula LiNi x Mn y Co z Lithium-nickel-manganese-cobalt mixed oxide represented by the formula LiNi x Co y Al z The cathode paste further comprises a metallic lithium mixed oxide selected from the group consisting of lithium-nickel-cobalt-aluminium mixed oxides of 02, 03, 04, 05, 06, 07, 08, 09, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200, 210, 220, 230, 240, 250, 260, 270, 280, 290, 300, 310, 320, 330, 340, 350, 360, 370, 380, 390, 400, 410, 420, 430, 440, 450, 460, 470, 480, 490, 500, 510, 520, 530, 540, 550, 560, 570, 580, 590, 600, 610, 620, 630, 640, 650, 660, 670, 680, 690, 700, 710, 720, 730, 740, 750, 760, 770, 780, 790, 800, 810, 820, 830, 840, 850, 860, 870, 880, 890, 900, 910, 920, 930, 940, 950, 960, 970, 980, 9
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a cathode paste, a method for its preparation, uses of the cathode paste, and a method for the preparation of an electrochemical energy storage cell using said cathode paste. [Background technology]

[0002] Lithium-ion cells are a type of energy storage element that is widely used. In general, an energy storage element is understood to be both an electrochemical cell capable of storing electrical energy and a battery with several electrically interconnected electrochemical cells capable of storing electrical energy. Each electrochemical cell generally comprises at least one positive electrode and at least one negative electrode, which are separated from each other by a separator.

[0003] In an electrochemical cell, an electrochemical energy-delivering reaction takes place, which consists of two electrically coupled but spatially separated partial reactions. One partial reaction, which takes place at a relatively low redox potential, takes place at the negative electrode, and one at a relatively high redox potential takes place at the positive electrode. During discharge, electrons are released at the negative electrode as a result of the oxidation process, resulting in an electron flow to the positive electrode via an external consumer, which in turn provides a corresponding amount of electrons. Thus, a reduction process takes place at the positive electrode. At the same time, due to charge balance, an ionic current corresponding to the electrode reaction takes place in the energy storage element. This ionic current crosses the separator and is realized by the ionically conductive electrolyte.

[0004] In secondary (rechargeable) electrochemical cells, this discharge reaction is reversible, so that the conversion of chemical energy produced during discharge to electrical energy can be reversed.

[0005] When the terms "anode" and "cathode" are used in reference to secondary electrochemical cells, the electrodes are named by their discharge function. Thus, the negative electrode in such energy storage elements is the anode and the positive electrode is the cathode.

[0006] A lithium-ion cell includes electrodes that can reversibly absorb and release lithium ions, and an electrolyte that contains lithium ions. Electrodes in lithium-ion cells are typically composed of conductive current collectors, electrochemically active components (often called active materials), and, if necessary, electrochemically inactive components. The electrochemically inactive components perform important functions in the electrode but are not involved in the storage of lithium or lithium ions.

[0007] The current collectors serve to electrically contact the electrochemically active components over as large an area as possible and usually consist of a metal foil, for example in ribbon form, or a metal foam, or a metal mesh, or a metal grid, or a metallized non-woven fabric.

[0008] Any material capable of absorbing and releasing lithium ions can be used as the active material of the electrode of a secondary lithium-ion cell. Prior art materials for the negative electrode (anode) of a secondary lithium-ion cell are in particular carbon-based materials capable of lithium intercalation, such as graphitic carbon or non-graphitic carbon materials. In addition, metallic and semi-metallic materials capable of alloying with lithium can be used. For example, the elements tin, antimony and silicon can form intermetallic phases with lithium. In particular, carbon-based active materials can also be combined with the metallic and semi-metallic materials mentioned above.

[0009] For the positive electrode (cathode) of secondary lithium-ion cells, metallic lithium mixed oxides, which may in particular contain nickel, are used as active materials. Lithium-nickel-manganese-cobalt oxide (NMC) and lithium-nickel-cobalt-aluminum oxide (NCA) are particularly common. Mixtures and derivatives of the above materials can also be used.

[0010] The electrochemically inactive components are first of all the electrode binder and the conductive agent. The electrode binder ensures the mechanical stability of the electrode and provides the contact between the particles of electrochemically active material and the current collector. Common electrode binders are often based on polyvinylidene difluoride (PVDF). The conductive agent, such as carbon black, has the function of increasing the electrical conductivity of the electrode.

[0011] Porous plastic films, for example made of polyolefins, polyesters, or polyetherketones, are particularly suitable as separators in lithium-ion cells. Nonwovens and fabrics made from these materials can also be used.

[0012] As an ionically conductive electrolyte, the lithium-ion cell may, for example, contain a mixture of organic carbonates in which a lithium salt is dissolved. A frequently used example of a suitable lithium salt is lithium hexafluorophosphate (LiPF6). Preferably, the electrodes and separators of the lithium-ion cell are impregnated with the electrolyte.

[0013] It is known to manufacture cathodes for lithium-ion cells or corresponding batteries using solvent-based cathode pastes that contain the cathode active material, a binder, and optionally a conductive agent such as carbon black. These cathode pastes are applied in a thin layer to a flat current collector, i.e. in particular a flat metal substrate, such as aluminum foil, and generally dried.

[0014] One very common class of electrode binders or binders is polyvinylidene difluoride (PVDF). The use of this binder class requires the use of aprotic, highly polar solvents. In this situation, the use of N-methylpyrrolidone (NMP) or N-ethylpyrrolidone (NEP) is very popular.

[0015] However, the use and processing of such cathode pastes is not without problems, in particular premature gelation of the cathode paste can occur, making subsequent processing more difficult, and can result in quality fluctuations in lithium-ion cells manufactured with the cathode pastes.

[0016] The main problem in this situation is the high hygroscopicity of the cathode active materials used. These materials, especially lithium nickel manganese cobalt oxide or lithium nickel cobalt aluminum oxide, react with ambient moisture to form strongly alkaline hydroxide compounds. These hydroxide compounds can then attack the relatively acidic hydrogen atoms of polyvinylidene difluoride, causing cross-linking reactions of the electrode binder. This can lead to viscosity changes in the cathode paste and premature gelation. Furthermore, the adhesive properties of the cathode paste are reduced, thereby rendering it unavailable for further use.

[0017] A conventional method to solve this problem is, for example, by chemical modification of polyvinylidene difluoride, for example by substitution of hydrogen atoms or copolymerization with another monomer, and polyvinylidene difluoride modified in this way is generally slower to react than unmodified polyvinylidene difluoride.

[0018] Alternatively, US 2013 / 0309570 A1 suggests adding inorganic additives such as alumina, zirconia, or vanadium oxide to the paste to avoid gelling of the cathode paste. As another option, US Pat. No. 7,829,219 B2 suggests adding a polymerization inhibitor in the form of a catechol derivative to the cathode paste.

[0019] However, these methods suffer from drawbacks because the composition of the resulting cathode is altered. In the first case, this is achieved by complex modifications of the PVDF, and in the other case by adding further components or foreign substances to the cathode paste, which may change the properties of the resulting cathode. For example, this may affect the bonding properties of the cathode paste to the current collector.

[0020] Another way to solve the above problem is to try to avoid the introduction of problematic moisture as much as possible during the production of the cathode. This can be done in particular by using suitable protective gases and a very dry atmosphere during the cathode production process. However, this is a technically complex and expensive measure during production and therefore disadvantageous from the point of view of the lithium-ion cell manufacturer. Summary of the Invention [Problem to be solved by the invention]

[0021] In contrast, the present invention aims at providing an improved cathode paste, in which the problems mentioned in the prior art are avoided. In particular, the cathode paste is intended to avoid quality fluctuations in the resulting lithium-ion cell or corresponding battery. Furthermore, problems in the manufacturing process that may arise due to changes in the state of the cathode paste should be avoided. Furthermore, a cathode paste should be provided in such a way that a less complicated manufacturing process for the lithium-ion cell is possible, while at the same time the quality and properties of the lithium-ion cell or corresponding battery, in particular the properties of the cathode, are consistently good. [Means for solving the problem]

[0022] This object is achieved by a cathode paste having the features set forth in claim 1. Advantageous embodiments of the cathode paste according to the invention will also be evident from the dependent claims. Furthermore, the above-mentioned problem is solved by a method for producing a cathode paste, by the use of said cathode paste for producing a lithium-ion cell and by a method for producing a lithium-ion cell with the cathode paste according to the invention according to the further auxiliary claims. Preferred embodiments of the method for producing a lithium-ion cell will also be evident from the further dependent claims.

[0023] The cathode paste according to the invention is intended for the manufacture of a cathode of a lithium-ion cell or a corresponding battery and has the following characteristics a. to d.: a. The cathode paste contains as an active material a compound of the formula LiNi x Mn y Co z Lithium-nickel-manganese-cobalt mixed oxides of formula LiNiO2, where x+y+z=1 and x≧0.6 x Co y Al z 02, where x+y+z=1 and x≧0.8, and mixtures of the above lithium mixed oxides; b. the cathode paste comprises a polyvinylidene difluoride based electrode binder; c. the cathode paste comprises a solvent comprising N-methylpyrrolidone (NMP) and / or N-ethylpyrrolidone (NEP); d. The solvent contains an organic additive component capable of neutralizing hydroxide ions and having a boiling point at atmospheric pressure within the range of 50°C to 210°C, preferably within the range of 100°C to 210°C; It is characterized by:

[0024] Metallic lithium mixed oxides are mixed oxides containing nickel in an atomic ratio of 60% or more. The inventors have been able to determine that, in particular, the use of such cathode active materials with a nickel content of more than 60% gives rise to the described problems of undesired crosslinking of the electrode binder, which makes further processing of the cathode paste in a coating process difficult or impossible.

[0025] In a preferred embodiment of the cathode paste according to the invention, lithium mixed oxides with high nickel content are used, which are commonly used in the manufacture of lithium-ion cells.For example, NMC-622 and NMC-811 are particularly preferred, and these numerical sequences refer to the atomic ratios of nickel, manganese and cobalt in the mixed oxide, i.e., 6:2:2 and 8:1:1, respectively.Another preferred example is NCA-811, which has nickel, cobalt and aluminum in a ratio of 8:1:1.

[0026] Experiments by the inventors have shown that adding the organic additive component to the cathode paste can greatly improve the properties of the cathode paste, thereby making the mixing process of the cathode paste and the coating process in the manufacture of cathodes easier and less costly. The organic additive component provides consistent quality and processability of the cathode paste, thereby avoiding fluctuations in the quality of the cathodes manufactured therewith. In particular, the organic additive component in the cathode paste prevents undesirable premature gelation of the cathode paste, which makes subsequent processing much more difficult.

[0027] The cathode paste according to the invention makes it possible to dispense with special technical measures during the processing of the cathode paste which are intended to suppress the influence of moisture and thereby to avoid undesirable gelling.

[0028] Due to the nature of the organic additive component with respect to neutralization of hydroxide ions, this additive component ensures that undesired crosslinking of PVDF is avoided. Furthermore, the boiling point of the organic additive component is preferably in the range of 50°C to 210°C, preferably in the range of 80°C to 210°C, particularly preferably in the range of 100°C to 210°C or in the range of 80°C to 150°C at atmospheric pressure, which ensures virtually complete evaporation of the organic additive component under the drying conditions used during the cathode manufacturing process. Thus, virtually no organic additive component remains in the coated and dried cathode. The properties of the finished cathode are therefore not affected by the organic additive component in the cathode paste. On the other hand, the organic additive component influences the viscosity properties of the cathode paste during the manufacture of the cathode paste according to the invention and during its processing, such that undesired crosslinking of PVDF is avoided. On the other hand, this facilitates the processing of the cathode paste. Additionally, the organic additive component facilitates, or even enables in the first place, storage and transportation of the finished cathode paste because the organic additive component prevents premature gelation of the cathode paste.

[0029] Overall, the invention in principle allows the production and processing of cathode pastes with commonly used materials, in particular lithium mixed oxides with a nickel content of 60% or more and polyvinylidene difluoride (PVDF) can be used as electrode binders with the solvents N-methylpyrrolidone (NMP) and / or N-ethylpyrrolidone (NEP), without the problems mentioned at the beginning. In particular, no additional dehumidification measures need to be taken in the cathode paste mixing and coating processes to prevent undesired crosslinking of the electrode binder. Furthermore, no further additives are required, such as polymerization inhibitors or inorganic additives such as aluminum oxide, zirconium oxide, vanadium oxide, etc., which would change the composition and thus the properties of the resulting cathode. Furthermore, it is not necessary to use specific modified PVDF polymers or copolymerized PVDFs as electrode binders, in which crosslinking is intended to be prevented. Therefore, in a particularly preferred embodiment, the cathode paste according to the invention does not contain further inorganic additives and / or polymerization inhibitors and / or does not contain modified PVDF polymers.

[0030] The cathode paste according to the invention therefore does not require special binder materials, which are associated with higher costs. Furthermore, when using the cathode paste according to the invention, technically complex solutions in the production of cathodes, such as drying chambers and protective atmospheres in the mixing and coating area, can be dispensed with. The use of organic additive components stabilizes the resulting cathode paste, which makes it easier to handle than conventional cathode pastes and improves storage and coating properties. This increases the reliability of the process, ensures seasonal independence, and also provides a consistent quality of the cathode paste and the cathodes that can be produced therewith, especially at somewhat higher ambient temperatures. Furthermore, the cathode paste according to the invention also provides economic advantages, since commercially available chemicals can be used and complicated technical measures are not required in the mixing and coating process.

[0031] The cathode paste according to the present invention is a non-aqueous electrode paste that includes one or more organic solvents.

[0032] The NMP and / or NEP used in the preparation of the cathode paste is preferably of battery grade quality. The solvent is particularly characterized by containing as little water as possible. For example, the solvent used may contain up to 300 ppm water, preferably less water.

[0033] In a particularly preferred embodiment, the cathode paste according to the invention has the following additional characteristics: a. the cathode paste is stable with respect to its viscosity characteristics for a period of at least 2 weeks, preferably at least 4 weeks, at room temperature; It is characterized by:

[0034] "Room temperature" in this context means a temperature in the range of 20°C to 25°C at a relative humidity of 20 to 50%. "Stable" in this context means that the viscosity (freshly measured at 200 / s (plate-plate 40 mm)) which can be determined based on values ​​from rheological measurements, changes by no more than 20%. For example, the viscosity can increase from 1.3 Pas to 1.5 Pas within 4 weeks.

[0035] The inventors have been able to show in comparative tests that the viscosity characteristics of the cathode paste according to the invention remain stable for several weeks, even during long-term storage at room temperature in a closed container. Over such longer periods, the flow properties of the cathode paste according to the invention do not change significantly. In particular, no detectable gelling of the cathode paste occurs, and the material remains homogeneously miscible and flowable. Furthermore, little or no settling of the paste components occurs. It is advantageous to store the cathode paste in a closed container during storage, so that evaporation of the solvent components of the cathode paste does not occur.

[0036] Due to the stable viscosity properties of the cathode paste according to the invention over a longer period, which may be, for example, more than four weeks, the processing of the cathode paste is greatly simplified. In particular, the cathode paste can be produced and stored, and used only when required. Furthermore, this allows the production, storage, and, if necessary, transportation of the cathode paste, so that it can be further processed at another location.

[0037] In one particularly preferred manner, the cathode paste according to the invention has the following additional characteristics a. and / or b.: a. the organic additive component is present in the solvent in a proportion of 0.1 to 10% by weight, preferably in a proportion of 0.5 to 7% by weight, particularly preferably in a proportion of 1 to 5% by weight; b N-methylpyrrolidone and / or N-ethylpyrrolidone are present in the solvent at a ratio of 60 to 99.9% by weight, preferably 80 to 99.5% by weight; The present invention is characterized by at least one of the following:

[0038] In a particularly preferred embodiment, the ratio of the organic additive component in the solvent is adjusted so that the organic additive component is added in a more than stoichiometric amount relative to the electrode binder or PVDF in the cathode paste. In general, a ratio of 5% by weight of the organic additive component in the solvent is sufficient. Depending on the mixing ratio in the cathode paste, particularly the ratio of the electrode binder in the cathode paste, a smaller amount may be sufficient. In a preferred embodiment, for example, 5% by weight of the organic additive component or 1.2% by weight of the organic additive component can be present in the solvent.

[0039] In a preferred embodiment, the solvent consists of only two components, the organic additive component and the actual solvent N-methylpyrrolidone (NMP) and / or N-ethylpyrrolidone (NEP), so that the ratio of the solvent NMP and / or NEP to the organic additive component sums to 100%. If necessary, further components can be present in the solvent, for example further organic solvents, or for example NMP and NEP can be present as a mixture. The use of only the solvent NEP may be preferred, since NEP is classified as less toxic than NMP.

[0040] In a further preferred embodiment, the cathode paste according to the invention has the following further characteristics a. to c.: a. the organic additive component is or comprises an organic acid, in particular acetic acid, preferably acetic anhydride, and / or oxalic acid and / or malonic acid; b. the organic additive component is or comprises a precursor of an organic acid, in particular an ester of an organic acid, preferably an ester of orthocarbonic and / or formic acid, or an anhydride of an organic acid, preferably acetic anhydride and / or maleic anhydride; c. the organic additive component is or comprises a CH acidic organic compound, in particular an ester and / or a diester and / or a ketone and / or a diketone and / or a nitrile and / or a dinitrile, and / or an organic halogen compound and / or a mixed-substitution compound, in particular methyl acetoacetate, diethyl malonate, chloroacetate, and / or ethyl acetoacetate; The present invention is characterized by at least one of the following: In particular, the organic additive component is one that is soluble in or readily miscible with NMP and / or NEP.

[0041] All of the preferred organic additive components according to the above characteristics a. to c. have the property of being able to neutralize hydroxide ions and thus reliably prevent crosslinking of polyvinylidene difluoride in the cathode paste. The chemical processes occurring in this process may vary, but as a result, the results of the cathode paste are prevented. In particular, this can occur by reactivity with moisture in an alkaline medium, or by reactivity with strongly alkaline compounds forming stable salts, or by reactivity with alkaline compounds or deprotonated PVDF by strongly acidic hydrogen atoms. Additionally, it may be preferred that the organic additive components, particularly the organic acids used as the organic additive components, are anhydrous or substantially anhydrous. The use of ethyl acetoacetate and / or acetic anhydride as organic additives has proven to be particularly advantageous in this context.

[0042] In a particularly preferred embodiment of the cathode paste according to the invention, the cathode paste has the following further characteristics a: a. The organic additive component is ethyl acetoacetate, and is present in the solvent at a ratio of 1 to 5% by weight, preferably 5% by weight; It is characterized by:

[0043] As an alternative, as in a particularly preferred embodiment of the cathode paste according to the invention, the cathode paste has the following additional characteristics: a. the organic additive component is acetic anhydride, and is present in the solvent at a ratio of 1 to 5% by weight, preferably 1.2% by weight; It is characterized by:

[0044] In both cases where ethyl acetoacetate was used as the organic additive component and where acetic anhydride was used as the organic additive component, our tests showed that no gelling of the paste occurred even after storing the cathode paste for a longer period of time, especially for more than 40 days. The material remained uniformly miscible and flowable, and therefore easily amenable to processing in the coating process.

[0045] With respect to the proportion of solvent in the cathode paste as a whole, the cathode paste according to the invention, in a particularly preferred manner, has the following further characteristics a: a. The ratio of the solvent in the cathode paste is within the range of 10 to 50% by weight, preferably within the range of 25 to 40% by weight, particularly within the range of 25 to 30% by weight; It is characterized by:

[0046] With respect to the overall cathode paste composition, the proportion of organic additive components may in particular be in the range of 0.3% to 2%.

[0047] The ratio of the solvents in the total cathode paste, and in particular the ratio of the organic additive components, can be appropriately adapted to the ratios of the other components, in particular the ratio of the organic additive components can be adapted to the amount of each active material in order to exceed the stoichiometric ratio.

[0048] With regard to the electrode binder, in a preferred embodiment, the cathode paste according to the invention has the following additional characteristics a. or b.: a. the polyvinylidene difluoride is a polyvinylidene difluoride homopolymer; b. the polyvinylidene difluoride comprises an ionically crosslinkable moiety; c. polyvinylidene difluoride has an average molecular weight in the range of 200,000 g / mol to 1,000,000 g / mol, preferably in the range of 400,000 g / mol to 850,000 g / mol; The present invention is characterized by at least one of the following:

[0049] Preferably, the electrode binder is PVDF. PVDF can be provided, for example, as a powder. PVDF materials commonly used in the manufacture of lithium-ion cells are particularly suitable as electrode binders. Preferably, the PVDF in this case has a high molecular weight, which is typical for this field of application. In particular, homopolymer PVDF can be used for typical battery applications.

[0050] The total amount of PVDF in the cathode paste is preferably in the range of 0.5% to 20% by weight, more preferably in the range of 1% to 10% by weight. In some preferred embodiments, the amount of PVDF in the total cathode paste may specifically be 1.5% ± 1% by weight.

[0051] It is also preferred that the cathode paste comprises a conductive agent, preferably conductive carbon black. The proportion of conductive carbon black in the cathode paste may be within the usual range. For example, the proportion of conductive carbon black, or conductive agent in general, may be within the range of 1% by weight to 30% by weight, particularly preferably 5% by weight to 20% by weight. In a particularly preferred embodiment of the cathode paste according to the invention, the proportion of conductive carbon black is 3% by weight ±1% by weight.

[0052] The present invention further comprises a method for producing a cathode paste according to the invention, characterized in particular by the organic additive component in the above-mentioned method, comprising the following method steps a. to g: Providing a solvent comprising N-methylpyrrolidone and / or N-ethylpyrrolidone and an organic additive component capable of neutralizing hydroxide ions and having a boiling point at atmospheric pressure in the range of 50° C. to 210° C.; b. dissolving a polyvinylidene difluoride based electrode binder in the solvent with stirring; c. Optionally, adding a conductive agent, in particular conductive carbon black; d.Formula LiNi x Mn y Co z Lithium-nickel-manganese-cobalt mixed oxides of formula LiNiO2, where x+y+z=1 and x≧0.6 x Co y Al z 02, where x+y+z=1 and x≧0.8, a lithium-nickel-cobalt-aluminum mixed oxide, and a mixture of the above lithium mixed oxides; e. mixing the lithium mixed oxide from step d. with the mixture obtained in step b. or c.; f. Optionally, adding additional solvent to the mixture obtained in step e in order to set a specific viscosity, in particular a viscosity in the range of 1.25 Pas-1.8 Pas (preferably measured at a shear rate of 200 / s using a dynamic viscosity measuring plate-plate (40 mm); g. optionally filtering the mixture obtained in step f.; Includes.

[0053] In this method, it is important that the active material, i.e. the metallic lithium mixed oxide, does not come into contact with the electrode binder PVDF before neutralization, because otherwise undesired crosslinking reactions may occur. Therefore, the metallic lithium mixed oxide is added after dissolving PVDF in a solvent containing the organic solvents NMP and / or NEP and organic additive components. The addition of the lithium mixed oxide to the mixture of PVDF and the solvent, which may also contain conductive carbon black, is preferably carried out stepwise and / or slowly to ensure that undesired crosslinking is avoided.

[0054] In step f., the described method optionally allows for setting a specific viscosity by adding additional solvent. The respective viscosity and / or its optional setting in process step f. can be adapted to the respective conditions and applications. A final filtration of the resulting mixture in process step g., for example using a sieving filter with a mesh size of 50-70 μm, may be useful depending on the application or may be omitted if necessary.

[0055] The present invention further comprises the use of the described cathode paste for producing a lithium-ion cell or for producing a corresponding battery, wherein the cathode paste according to the invention is applied to a current collector and dried to obtain the cathode of the cell.

[0056] Finally, the invention includes a method for producing a lithium-ion cell having at least one cathode and at least one anode, or a method for producing a corresponding battery. In principle, this method can be carried out in the same way as conventional methods for producing lithium-ion cells, in which a cathode paste is used to produce the cathode. A particular feature of the method according to the invention is that a cathode paste according to the invention is used to produce or provide at least one cathode, which cathode paste is characterized by the further organic components described. In this method, this cathode paste is applied to a current collector and dried. The remaining steps for producing a lithium-ion cell are well known to those skilled in the art.

[0057] The current collector of the cathode may in particular be an aluminum foil or mesh or other layer, which has a thickness of, for example, between 1 μm and 500 μm. The cathode paste according to the invention can be applied to this current collector in various ways, preferably a thin layer is applied during application. The layer thickness may, for example, be in the range of 25 μm to 150 μm. A conventional doctor blade process (doctor blade coating) or application with a slot nozzle can be used for this purpose. Of course, other coating processes are also possible. The layer is then dried, during which the organic solvent (NMP and / or NEP) and the organic additive components evaporate. The resulting cathode layer then adheres firmly to the current collector.

[0058] The preparation of the anode, the arrangement of the separator and the introduction of the electrolyte, as well as, if necessary, further steps for producing a lithium-ion cell, such as contacting the electrodes, can be carried out in a manner known per se.

[0059] In a particularly preferred embodiment of the method according to the invention, the method comprises the following further features a.: a. The cathode paste after application to the current collector is dried at a temperature within the range of 50° C. to 150° C., preferably within the range of 80° C. to 130° C., and particularly within the range of 100° C. to 120° C.; It is characterized by:

[0060] During this drying step, the solvent consisting of the organic solvents NMP and / or NEP and the organic additive components are evaporated. This means that the organic additive components and the actual solvents NMP and / or NEP are practically no longer present in the resulting cathode. Thus, the addition of the organic additive components according to the invention does not introduce additional substances into the cathode that may affect the properties of the cathode.

[0061] The organic additive components are characterized in that they can evaporate during the drying step provided in conventional cathode manufacturing methods, since the boiling points of the organic additive components are in the range of 50°C to 210°C. Under certain circumstances, the drying conditions, in particular the temperature during the drying process, can be adapted to the organic additive components used in each case, due to their respective boiling points. In this situation, additive components with relatively low boiling points are suitable for processes operated at relatively low temperatures during drying. If the additive components have relatively high boiling points, the drying temperature should be selected accordingly.

[0062] Their boiling points make the particularly preferred organic additives ethyl acetoacetate and acetic acid or glacial acetic acid suitable in conventional manufacturing processes where drying temperatures in the range of, for example, 100° C. to 120° C. are used.

[0063] In a particularly preferred embodiment of the method according to the invention, the method comprises the following further features a.: a. the formation of at least one cathode is carried out at atmospheric pressure and / or under normal air conditions; It is characterized by:

[0064] As already explained above, the use of the organic additive components according to the invention may make technically complex measures unnecessary to avoid undesired crosslinking reactions of PVDF, which occur in particular due to the strong hygroscopicity of the active material of the cathode, i.e. the lithium mixed oxides, in particular with a high nickel content. Thus, when the cathode paste according to the invention is used in the manufacturing process of lithium-ion cells, special preventive measures such as inert gas and / or very dry atmospheres are not necessary, since the organic additive components prevent crosslinking of PVDF. Thus, the manufacturing or mixing process of the cathode paste and the application process of the cathode paste to the current collector can be carried out under atmospheric conditions and / or under normal air conditions. This allows the design of a manufacturing process with the cathode paste according to the invention in a less complex way, while at the same time ensuring a consistent quality of the cathodes and therefore of the resulting lithium-ion cells.

[0065] Further features and advantages of the invention are shown by the following description of examples of embodiment in conjunction with the drawings, where the individual features can be realized either separately from each other or in combination with one another. [Brief description of the drawings]

[0066] [Figure 1] 1 illustrates an exemplary method for applying the cathode paste of the present invention to a current collector. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0067] The inventors have conducted various comparative tests to compare the resulting viscosity characteristics of the cathode paste according to the present invention with conventional cathode pastes after each longer period of time.

[0068] A comparative paste having no organic additive component and a cathode paste according to the present invention were prepared according to the following description. EXAMPLES

[0069] a) Comparative cathode paste (NMC-622) containing no organic additive components In a plastic container, 142.5 g of N-ethylpyrrolidone (NEP) or N-methylpyrrolidone (NMP) was weighed as a solvent, and 7.5 g of PVDF powder (Kynar HSV1810; Arkema, France) was added to the solvent under vigorous stirring until the PVDF powder was completely dissolved. This solution was mixed with 15 g of conductive carbon black (LiTX200, Cabot, USA) and stirred vigorously until a homogeneous mixture (carbon black paste) was obtained. 720 g of NMC-622 cathode active material (purchased from Umicore, Brussels, Belgium) was weighed into a mixing vessel. To this material, the carbon black paste was added in stages. After each addition stage, the resulting mixture was kneaded in a double planetary mixer until the material was uniformly dispersed and agglomerate-free paste was obtained. 40 g of additional solvent (NEP or NMP) was added to set the specified final viscosity (the same solid content was set in all cases). The paste was filtered and then rheologically tested for the presence of aggregates. The paste was stored in a closed plastic container for further testing. After 28 days of storage at 22°C and 20-30% room humidity, a clear gelation of the paste was observed. The material was solid and no longer homogeneously mixable. Flowability was no longer present.

[0070] b) Cathode paste with NEP or NMP and ethyl acetoacetate (NMC-622) In a plastic container, 7.13 g of ethyl acetoacetate (AEE) and 135.37 g of N-ethylpyrrolidone (NEP) or N-methylpyrrolidone (NMP) were weighed out. To this solvent mixture, 7.5 g of PVDF powder (Kynar HSV1810; Arkema, France) was added under vigorous stirring until the PVDF powder was completely dissolved. This solution was mixed with 15 g of conductive carbon black (LiTX200, Cabot, USA) and stirred vigorously until a homogeneous mixture (carbon black paste) was obtained. 720 g of NMC-622 cathode active material (purchased from Umicore, Brussels, Belgium) was weighed into a mixing vessel. To this material, the carbon black paste was added in stages. After each addition stage, the resulting mixture was kneaded in a double planetary mixer until the material was uniformly dispersed and agglomerate-free paste was obtained. 40 g of additional solvent (AEE and NEP or NMP in a 1:19 ratio) was added to set the specified final viscosity (the same solid content was set in all cases). The paste was filtered and then rheologically tested for the presence of aggregates. The paste was stored in a closed plastic container for further testing. After storage for 43 days at 22°C and 20-30% room humidity, no gelation of the paste was observed. The material settled slightly and was homogeneously mixable. Fluidity was still present.

[0071] c) Cathode paste with NEP or NMP and acetic anhydride (glacial acetic acid) (NMC-622) In a plastic container, 1.71 g of acetic acid (glacial) and 140.79 g of N-ethylpyrrolidone (NEP) or N-methylpyrrolidone (NMP) were weighed out. To this solvent mixture, 7.5 g of PVDF powder (Kynar HSV1810; Arkema, France) was added under vigorous stirring until the PVDF powder was completely dissolved. This solution was mixed with 15 g of conductive carbon black (LiTX200, Cabot, USA) and stirred vigorously until a homogeneous mixture (carbon black paste) was obtained. 720 g of NMC-622 cathode active material (purchased from Umicore, Brussels, Belgium) was weighed into a mixing vessel. To this material, the carbon black paste was added in stages. After each addition stage, the resulting mixture was kneaded in a double planetary mixer until the material was uniformly dispersed and agglomerate-free paste was obtained. Additional solvent (glacial acetic acid mixed with NEP or NMP in a ratio of 3:247) was added to set the specified final viscosity (the same solid content was set in all cases). The paste was filtered and then rheologically tested for the presence of aggregates. The paste was stored in a closed plastic container for further testing. After storage for 41 days at 22°C and 20-30% room humidity, no gelation of the paste was observed. The material had some settling and was homogeneously mixable. Fluidity was still present.

[0072] d) Comparative cathode paste (NMC-811) having no organic additive components A carbon black paste was prepared as in Example a). 720 g of cathode active material NMC-811 (purchased from Umicore, Brussels, Belgium) was weighed into a mixing vessel. The material was further processed to obtain a homogeneous paste and tested as in Example 1. After 27 days of storage at 22°C and 20-30% room humidity, gelation of the paste was observed. The material was solid and no longer homogeneously mixable. Flowability was no longer present.

[0073] e) Cathode paste with NEP or NMP and ethyl acetoacetate (NMC-811) A carbon black paste was prepared as in Example b). 720 g of cathode active material NMC-811 (purchased from Umicore, Brussels, Belgium) was weighed into a mixing vessel. The material was further processed to obtain a homogeneous paste and tested as in Example b). After storage for 36 days at 22°C and 20-30% room humidity, no gelation of the paste was observed. The material was homogeneously mixable. The fluidity was very good. Overall, these tests demonstrated that the inclusion of an organic additive component in the cathode paste solvent reliably prevented undesirable gelling.

[0074] Figure 1 shows one representative possibility for the further processing of the cathode paste according to the invention in the production of lithium-ion cells: the cathode paste is applied to a current collector in a doctor blade process and then dried.

[0075] First, the cathode paste 1 is prepared according to the above description, for example according to embodiment b) or c) or e). The cathode paste 1 is placed in a plastic container 10 and homogenized using a stirrer 20 (step A).

[0076] To produce the cathode, the cathode paste 1 is applied as a thin layer to a current collector 2, in particular an aluminum foil. For this, the current collector 2 is placed on a carrier 30 and the cathode paste 1 is applied uniformly as a thin layer to the current collector 2 by means of a doctor blade 40 (step B).

[0077] The cathode paste layer is subsequently dried at a temperature in the range of 50° C. to 150° C. Drying at a temperature in the range of 100° C. to 120° C. is particularly preferred. Depending on the circumstances, drying can take place for a period of a few minutes to about an hour, for example 5 to 60 minutes. During this drying, the solvent evaporates together with the organic solvent NMP or NEP and the organic additive components. This process gives a finished cathode 100 in which the cathode paste 1 has been applied to the current collector 2 and the solvent has evaporated. This cathode 100 can be further used in methods known per se for producing functional lithium-ion cells.

Claims

1. A cathode paste (1) for manufacturing a cathode of a lithium-ion cell, said paste having the following characteristics: a. The cathode paste (1) contains, as an active material, a compound represented by the formula LiNi x Mn y Co z O 2 Lithium-nickel-manganese-cobalt mixed oxides of the formula LiNi x Co y A z O 2 wherein x+y+z=1 and x≧0.8; and mixtures of said lithium mixed oxides; b. The cathode paste (1) contains polyvinylidene difluoride as an electrode binder or contains an electrode binder based on polyvinylidene difluoride; c. The cathode paste (1) contains a solvent including N-methylpyrrolidone and / or N-ethylpyrrolidone; d. the solvent comprises an organic additive component capable of neutralizing hydroxide ions and having a boiling point at atmospheric pressure within the range of 50° C. to 210° C.; The cathode paste (1) having

2. Further features: a. said cathode paste (1) is stable with respect to its viscosity characteristics at room temperature for a period of at least 2 weeks, preferably at least 4 weeks; 2. The cathode paste of claim 1 having the formula:

3. Further features: a. the organic additive component is present in the solvent in a proportion of 0.1 to 10% by weight, preferably in a proportion of 0.5 to 7% by weight, particularly preferably in a proportion of 1 to 5% by weight; b. The N-methylpyrrolidone and / or the N-ethylpyrrolidone are present in the solvent in a ratio of 60 to 99.9% by weight, preferably 80 to 99.5% by weight; The cathode paste of claim 1 having at least one of:

4. Further features: a. the organic additive component is or comprises an organic acid, in particular acetic acid, preferably acetic anhydride, and / or oxalic acid and / or malonic acid; b) the organic additive component is or comprises a precursor of an organic acid, in particular an ester of an organic acid, preferably an ester of orthocarbonic and / or formic acid, or an anhydride of an organic acid, preferably acetic anhydride and / or maleic anhydride; c) the organic additive component is or comprises a C-H acidic organic compound, in particular an ester and / or a diester and / or a ketone and / or a diketone and / or a nitrile and / or a dinitrile, and / or an organic halogen compound and / or a mixed-substitution compound, in particular methyl acetoacetate, diethyl malonate, chloroacetate, and / or ethyl acetoacetate; The cathode paste of claim 1 having at least one of:

5. Further features: a. the organic additive component is ethyl acetoacetate; b. the organic additive component is acetic anhydride; The cathode paste of claim 1 having at least one of:

6. Further features: a. the organic additive component is ethyl acetoacetate, present in the solvent in a proportion of 1 to 5% by weight, preferably 5% by weight; 2. The cathode paste of claim 1 having the formula:

7. Further features: a. the organic additive component is acetic anhydride and is present in the solvent in a proportion of 1 to 5% by weight, preferably 1.2% by weight; 2. The cathode paste of claim 1 having the formula:

8. Further features: a. The ratio of the solvent in the cathode paste (1) is in the range of 10 to 50% by weight, preferably in the range of 25 to 40% by weight, particularly in the range of 25 to 30% by weight; 2. The cathode paste of claim 1 having the formula:

9. Further features: a. the polyvinylidene difluoride is a polyvinylidene difluoride homopolymer; b. the polyvinylidene difluoride comprises an ionically crosslinkable component; The cathode paste of claim 1 having at least one of:

10. Further features: a. the cathode paste (1) contains a conductive agent, preferably conductive carbon black; 2. The cathode paste of claim 1 having the formula:

11. A method for producing a cathode paste (1) according to any one of claims 1 to 10, comprising the following method steps: a. providing a solvent comprising N-methylpyrrolidone and / or N-ethylpyrrolidone and an organic additive component capable of neutralizing hydroxide ions and having a boiling point at atmospheric pressure in the range of 50° C. to 210° C.; b. dissolving a polyvinylidene difluoride based electrode binder in the solvent with stirring; c. Optionally, adding a conductive agent, especially conductive carbon black; d. Formula LiNi x Mn y Co z O 2 Lithium-nickel-manganese-cobalt mixed oxides of the formula LiNi x Co y A z O 2 a metal lithium mixed oxide selected from the group consisting of lithium-nickel-cobalt-aluminium mixed oxides of formula (I) where x+y+z=1 and x≧0.8, and mixtures of said lithium mixed oxides; e. mixing the lithium mixed oxide from step d. with the mixture obtained in step b. or c.; f. Optionally, adding additional solvent to the mixture obtained in step e. to adjust to a specific viscosity; g. Optionally, filtering the mixture obtained in step f.; A manufacturing method comprising:

12. Use of the cathode paste (1) according to any one of claims 1 to 10 for manufacturing a lithium-ion cell, wherein the cathode paste (1) is applied to a current collector (2) and dried to obtain the cathode of the cell.

13. 11. A method for producing a lithium-ion cell having at least one cathode and at least one anode, characterized in that a cathode paste (1) according to any one of claims 1 to 10 is applied to a current collector (2) and dried to form the at least one cathode.

14. Further features: a. The cathode paste (1) is dried at a temperature in the range of 50°C to 150°C, preferably in the range of 80°C to 130°C, particularly in the range of 100°C to 120°C; 14. The method of claim 13, comprising:

15. Further features: a. the formation of said at least one cathode is carried out at atmospheric pressure conditions and / or under normal air conditions; 14. The method of claim 13, comprising: